Visiting EFL Class: The Use of Sentence-Soup Game in Writing Class - Efendi, Lelina; Wirabhakti, Agus (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2015)
The present quasi experimental study was conducted to describe how theimplementation of sentence soup game in the teaching writing and to determine the significant difference of the students’ achievement according to their pre-test and posttest result. The sample of study was 70 eighth grade students of SMPN 4 PalimananCirebon. A pre-test and post-test equivalent group design was used to compare the achievement of two groups. The collected data was statistically analyzed by t test formula. The result showed that: 1).The implementation of sentence soup game assessed gave positive effect in teaching writing. It evidenced if students got advantages in this learning with playing activity. 2a).There was no significant difference of the students’ pre-test result. Where null hypothesis was accepted, the tobtained was less than the tcritical (0,980 < 1,667). 2b). There was significant difference of the students’ post-test result. Where null hypothesis was rejected, the tobtained higher than tcritical (2,692 > 1,667). The students’ performance of experimental group was better based on the difference between the mean scores. The mean of experimental group was 5,5 on pre-test and 7,4 on post-test, hence control group was 5,0 on pre-test and 6,7 on post-test. It indicated if teaching English writing through sentence soup game enhanced the achievement level of the students.